Normal obstetric outcome in neurofibromatosis-1 complicating pregnancy - G.S., Anitha; V.R., Manjulatha; Naik, Kusuma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Neurofibromatosis (NF), a genetic disorder, has increased risk of obstetric complications as well as aggravation of maternal disease. However, here is a case of Neurofibromatosis associated with normal obstetric outcome despite the aggravation of dermatological lesions and a history of previous pregnancy with anomalous baby.